2018
DOI: 10.1097/lgt.0000000000000430
|View full text |Cite
|
Sign up to set email alerts
|

Preference for Human Papillomavirus Self-Collection and Papanicolaou: Survey of Underscreened Women in North Carolina

Abstract: Overall positive attitudes toward HPV self-collection compared with Pap testing among underscreened women suggest that self-collection is a promising option to increase cervical cancer screening in this high-risk population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 24 publications
(25 reference statements)
1
23
0
Order By: Relevance
“… 26 27 29 35–37 39 40 43 46 52 54 57 59 61–64 66 70 83 87 89 91 93 95 96 Furthermore, one study acknowledged that participants self-selected to participate with the knowledge that self-collection would be a critical component of the study, so there may have been some selection bias towards acceptability of the self-test. 43 One study assessed test–retest reliability and content validity of acceptability measures, 64 but psychometric properties of acceptability were not conducted consistently across studies. Thirty-two articles reported that their results were not transferable to the study population or entire geographic population.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“… 26 27 29 35–37 39 40 43 46 52 54 57 59 61–64 66 70 83 87 89 91 93 95 96 Furthermore, one study acknowledged that participants self-selected to participate with the knowledge that self-collection would be a critical component of the study, so there may have been some selection bias towards acceptability of the self-test. 43 One study assessed test–retest reliability and content validity of acceptability measures, 64 but psychometric properties of acceptability were not conducted consistently across studies. Thirty-two articles reported that their results were not transferable to the study population or entire geographic population.…”
Section: Resultsmentioning
confidence: 99%
“…35 3642 43 52 54 56 58 59 62 65 68 69 71 74 77-86 88 89 91-93 95 The most frequently cited reasons for preferring self-sampling over clinician sampling were less pain or physical discomfort, 29 31 32 34-37 39 43 44 52 57 58 65 70 71 73 77-80 86 88-91 93-95 ease of use, convenience, ability to perform the test in private 28 29 31-33 36 39 42 46 52 57 59 62 74 77 81 89 90 94 and less embarrassment or anxiety. 27 28 31 33 35 37 39 40 46 52 59 65 69 70 72 73 77-80 89-91…”
mentioning
confidence: 99%
“…Various study designs were used to elicit this preference, including 15 cross-sectional survey studies (35)(36)(37)(38)(39)(40)(41)(42)(43)(44)(45)(46)(47)(48)(49) (56), and one mixed methods study (57).…”
Section: Screening Modality (N ¼ 23)mentioning
confidence: 99%
“…All non-focus group studies reported the percentage of participants who preferred the HPV self-test to the Pap test (35)(36)(37)(38)(39)(40)(41)(42)(43)(44)(45)(46)(47)(48)(49)(54)(55)(56)(57). Percentages ranged from 10% (45) to over 90% (54).…”
Section: Screening Modality (N ¼ 23)mentioning
confidence: 99%
See 1 more Smart Citation